Tahun Yubileum menjadi Momen Pengharapan - Blasius Superma Yese (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
Throughout the year 2025, the Catholic Church is undergoing an Ordinary Jubilee Year. This Jubilee Year was opened on December 24, 2024, and will be closed on January 6, 2026. This Jubilee Year is the first ordinary jubilee in the third millennium. The mystery of faith that is contemplated in it is the mystery of the incarnation of the Word becoming Man in the person of Jesus Christ. Realizing the importance of the mystery of faith that is contemplated in this Jubilee Year, by using library research, the author collects and reads various writings about jubilees, especially the Ordinary Jubilee 2025. In this writing, we will look at the concept of jubilee, both in the scriptures and as intended by the Catholic Church. This writing also briefly describes the theme contemplated in the Jubilee Year 2025, as well as what needs to be done to fill this jubilee year.